Aging With Mental Disorders in the Criminal Justice System: A Content Analysis of the Empirical Literature - Maschi, Tina (International journal of offender therapy and comparative criminology, 2019)
To fill a current gap in the literature on aging, mental health, and the criminal justice system, a content analysis of international peer-reviewed research studies was conducted. A comprehensive literature search was conducted to identify English language research studies published in 2018-19. Forty-four articles were located using keyword search terms, such as aging, mental health, and criminal justice. The methods and major findings were analyzed using deductive and inductive approaches. It was found that the majority of the research studies were conducted in the United States and England. The results of the inductive analyses revealed major themes related to mental health detection and access to services, comorbid conditions, and the relationship of age, mental health, criminal behavior, and the social determinants of mental health. Findings from this review have significant implications for advancing epidemiological research, practice, and policy, especially as it relates to the influence of the social determinants of health of aging on life course mental health and criminal justice involvement. Research findings about the correlates and consequences of the social determinants of health, especially as it relates to aging, mental health, and criminal justice involvement, can be used to inform prevention and intervention efforts that target the social determinants of life course health and criminal justice involvement. It also provides a comprehensive assessment of the m methods used in prior studies to help improve future studies in this important area of investigation.